Diversité des capitalismes et dispositifs institutionnels environnementaux - Luc Elie (Revue de la Régulation)
This thesis contributes to the diachronic and synchronic analysis of the links between the forms of capitalism and environment. The first chapter proposes to highlight the manner in which the coevolution between capitalism and environment was carried out by crossing the theoretical and empirical contributions of the régulation school with environmental history and ecological economics studies. We reveal that the different historical forms of capitalism have led to extensive and differentiated environmental consequences. Conversely, it turns out that the relationships with the environment have had a major influence on the forms of capitalism, especially through institutional environmental devices (EID). The second chapter aims at deciphering in which extent these devices undergo a process of differentiated adoption depending on the contemporary forms of capitalism within which they take place. In this framework, some degree of correlation appears between our EID based typology of countries and Amable’s typology of capitalism. Finally, the third chapter focuses on how levels of inequality, which are largely dependent on different forms of capitalism, can influence the adoption of EID. By means of an econometric analysis, we attempt to determine which mechanisms are most likely to explain this phenomenon.